2021
DOI: 10.1016/j.ecoenv.2021.112035
|View full text |Cite
|
Sign up to set email alerts
|

Traffic generated emissions alter the lung microbiota by promoting the expansion of Proteobacteria in C57Bl/6 mice placed on a high-fat diet

Abstract: Air pollution has been documented to contribute to severe respiratory diseases like asthma and chronic obstructive pulmonary disorder (COPD). Although these diseases demonstrate a shift in the lung microbiota towards Proteobacteria, the effects of traffic generated emissions on lung microbiota profiles have not been well-characterized. Thus, we investigated the hypothesis that exposure to traffic-generated emissions can alter lung microbiota and immune defenses. Since a large population of the Western world co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…In our study, Proteobacteria , Firmicutes , Actinobacteria and Bacteroidetes were the top four relative abundances of bacteria in the lungs of control mice. We found that the lungs of control mice were rich in Lactobacillus , which was significantly reduced after sTBI, consistent with others [ 35 ]. Lactobacillus is a kind of probiotic, which has the functions of anti-inflammatory, anti-infection and regulating immune function, as a therapeutic approach to the prevention of lung diseases like asthma and allergic reactions, viral infections and chronic obstructive pulmonary disease [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, Proteobacteria , Firmicutes , Actinobacteria and Bacteroidetes were the top four relative abundances of bacteria in the lungs of control mice. We found that the lungs of control mice were rich in Lactobacillus , which was significantly reduced after sTBI, consistent with others [ 35 ]. Lactobacillus is a kind of probiotic, which has the functions of anti-inflammatory, anti-infection and regulating immune function, as a therapeutic approach to the prevention of lung diseases like asthma and allergic reactions, viral infections and chronic obstructive pulmonary disease [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Proteobacteria are spoilage bacteria and often appear in the intestines of humans and animals. When the intestines are exposed to contaminants, Proteobacteria increase significantly [ 41 ]. Proteobacteria can affect the function of the gastrointestinal tract and cause many diseases [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…16S rRNA gene sequencing reads (in fastq format) were analyzed using methods previously established by our lab [ 85 ]. Downstream statistical analysis of the data was performed to determine alpha diversity analysis (diversity within the sample) by generating the plots for Chao 1 and ACE index (for species richness), Shannon index (for species diversity), and evenness index (for species evenness).…”
Section: Methodsmentioning
confidence: 99%